(untitled) (Olhar de Professor, 2012)
This article deals with the assessment of foreign language teaching, aiming to trace the method in which the teaching of English focused on aviation functions, with emphasis on ﬂight security. After a theoretical discussion of the evaluation of learning and the main approaches to teaching foreign languages, we present trends in research on the evaluation of English teaching focused on the area of aviation, resulting from a literature survey from1990 to 2009 of the studies that are part of the CAPES archive of academic theses and dissertations concerning the evaluation of English teaching in the area of aviation. Our research shows the weakness of this area of study, speciﬁcally concerning ﬂight safety aspects.